Sylvian Fissure Meningiomas: Case Report and Literature Review - Cai, Chengwei; Zhu, Zhoule; Guo, Xinxia; Guo, Xiaoming; Jiang, Hongjie; Zheng, Zhe; Zhang, Jianmin; Shao, Anwen; Zhu, Junming (Frontiers in Oncology, 2020)
Meningiomas are primary intracranial tumors derived from the arachnoid cap cells or meningothelial cells and usually display dural attachment. However, a small proportion of meningiomas arise from the Sylvian fissure do not manifest dural attachment. Sylvian fissure meningiomas are relatively rare and have differential characteristics as compared with typical meningiomas. Herein, we reported a special case of atypical meningioma in the Sylvian fissure, who showed non-enhancement after contract management. The patient was a 30-year-old woman with a 2-year history of seizures. Preoperative computerized tomography and magnetic resonance imaging scans showed a calcific, non-enhancing lesion in the right insula lobe. The lesion was excised surgically for seizure control. Intraoperatively, the tumor was observed to be closely adhered to the middle cerebral artery (MCA), resulting in mild arterial damage. A case of Sylvian fissure meningioma was ultimately diagnosed by histopathological examination of the resected specimens. Sylvian fissure meningiomas are closely associated with the MCA and exhibit unusual imaging characteristics. Preoperative misdiagnosis may have serious adverse consequences and may result in incorrect surgery. To improve awareness of Sylvian fissure meningiomas on the differential diagnosis of Sylvian fissure lesions among clinicians, we present this report and briefly summarize previously reported cases to describe the clinical, pathological, radiological, and surgical features.